Canada : a very short introduction - Wright, Donald A., 1965- (Oxford : Oxford University Press, 2020)
A bilingual, multicultural, and multinational nation, Canada borders the United States, reaches into the Arctic, and stretches across six time zones. Drawing on Canadian history, politics, and literature, Donald Wright explores the Canadian story and identity, from the arrival of the first Indigenous peoples to contemporary climate politics.
Also issued in print: 2020.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 30, 2020).
Keywords: Canada